2023
DOI: 10.15586/aei.v51i6.971
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrokaempferol attenuates LPS-induced inflammation and apoptosis in WI-38 cells

Qiao Wang,
Liwen Zhang,
Ping Pang

Abstract: Background: Globally, pneumonia has been associated as a primary cause of mortality in children aged less than 5 years. Dihydrokaempferol (DHK) has been proposed for being correlated with the process of various diseases. Nevertheless, whether DHK has a role in the progression of infantile pneumonia remains unclear. This study aimed at exploring whether DHK was involved in the progression of infantile pneumonia. Methods: Human fibroblast cells WI-38 were treated with lipopolysaccharide (LPS). The viability of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similarly, astragalin [ 38 ], daidzein [ 39 ], and adenosine [ 40 ] have also been demonstrated to attenuate the endothelial inflammatory response. In addition, anti-inflammatory activity was observed for daphnoretin [ 41 ], dihydrokaempferol [ 42 ], jasmonic acid [ 43 ], and kaempferol 3- O -rutinoside [ 44 ], but their modes of action on endothelial activation remain largely unknown. Interestingly, among compounds mentioned above, previous studies have provided evidence that kaempferol [ 45 ], astragalin [ 46 ], apigenin [ 47 ], daidzein [ 48 ], adenosine [ 49 ], and salicylic acid [ 50 ] exerts protective effects on myocardial I/R injury in experimental animals, depending on the anti-inflammation and anti-oxidative stress activities of these natural molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, astragalin [ 38 ], daidzein [ 39 ], and adenosine [ 40 ] have also been demonstrated to attenuate the endothelial inflammatory response. In addition, anti-inflammatory activity was observed for daphnoretin [ 41 ], dihydrokaempferol [ 42 ], jasmonic acid [ 43 ], and kaempferol 3- O -rutinoside [ 44 ], but their modes of action on endothelial activation remain largely unknown. Interestingly, among compounds mentioned above, previous studies have provided evidence that kaempferol [ 45 ], astragalin [ 46 ], apigenin [ 47 ], daidzein [ 48 ], adenosine [ 49 ], and salicylic acid [ 50 ] exerts protective effects on myocardial I/R injury in experimental animals, depending on the anti-inflammation and anti-oxidative stress activities of these natural molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DHK can ameliorate severe acute pancreatitis through the Keap1/Nrf2 pathway [11]. DHK also attenuates LPS-induced inflammation and apoptosis in Wl38 cells [12] and has apoptotic effects on synoviocytes. In addition, DHK detoxicates CCl4 by inhibiting RARP-1, thereby affecting multiple downstream pathways and cytokine-induced liver fibrosis [13].…”
Section: Introductionmentioning
confidence: 99%